Far-field fluorescence microscopy at the macromolecular scale - Hell, S; Willig, K; Hofmann, M; Eggeling, C; Westphal, V (Optical Society of America, 2006)
Since its discovery by Abbe in 1873, the microscopy diffraction barrier has received a lot of attention. In this lecture, we discuss the principle of fundamentally breaking the diffraction barrier through reversible saturable optical (fluorescence) transitions (RESOLFT). © 2005 Optical Society of America.